The Construction and Application of Functional Indexes of Colleges and Universities in the Development of Sports Industry — Analysis Based on Fuzzy Comprehensive Evaluation Method. Issue 8 (2017) - Wang, Dong-Bo; Lu, Wen-Juan
No abstract available